Sociological Condition of Conan Doyle and Its Relation to the Setting of a Study in Scarlet Novel - Cicih Nuraeni; Eva Kristina Sagala (Lembaga Riset dan Pengabdian Masyarakat Institut Bisnis Nusantara, 2019)
Literature and society is relating each other. A literary work, such as novel, emerges from society and social condition. A Study in Scarlet is a famous novel about detective story. Its author’s life, surely has an important role to this novel. The objective of this research is to analyze socialogical condition of Conan Doyle. This analysis takes the data from novel A Study in Scarlet written by Conan Doyle. The supported theories collected through library and internet research. The researchers uses descriptive qualitative method in analyzing this novel. Result of this analysis are, first, sociological background of Conan Doyle are; a 28 years old man, live in London, study of medicine, live good in the middle class of economic and work as a surgeon and researchers. Second, Conan Doyle’s reason in writing this novel are for beauty, foraging and imitate other’s behavior. Third, Conan Doyle’s social condition relates to the setting of this novel. Setting of place mostly in London, setting of time commonly in war time and setting of social concerns with war condition Abstrak Sastra dan kehidupan bermasyarakat berkaitan satu sama lain. Sebuah karya sastra, seperti baru, muncul dari masyarakat dan kondisi sosial. A Study in Scarlet adalah sebuah novel terkenal tentang cerita detektif. Kisah nyata penulis pasti memiliki peran penting untuk novel ini. Tujuan dari penelitian ini adalah untuk menganalisis kondisi socialogical dari Conan Doyle. Analisis ini mengambil data dari novel A Study in Scarlet ditulis oleh Conan Doyle. teori yang didukung dikumpulkan melalui perpustakaan dan penelitian internet. Penulis menggunakan metode deskriptif kualitatif dalam menganalisis novel ini. Hasil analisis ini adalah pertama, latar belakang sosiologis Conan Doyle adalah; 28 tahun pria tua, tinggal di London, studi kedokteran, hidup baik di kelas menengah ekonomi dan bekerja sebagai dokter bedah dan penulis. Kedua, alasan Conan Doyle dalam menulis novel ini adalah untuk kecantikan, mencari makan, dan meniru perilaku lain. Ketiga, kondisi sosial Conan Doyle berkaitan dengan pengaturan novel ini. Pengaturan tempat sebagian besar di London, pengaturan waktu yang biasa dalam waktu perang dan pengaturan dari kepedulian sosial dengan kondisi perang.